Squirrel wars : [videorecording (DVD)] and how to win them - Harrison, George H. (Harrison Productations, 2004)
Squirrel wars is a 40- minute PBS television event hosted by naturalist George Harrison which explores the impact squirrels have on people, often causing outrageous human behavior. Scenes of foolish battles people wage on the pests are followed by practical, safe and easy solutions for both people and squirrels.